Review of the strategic approach to the problem of poverty in Montenegro - Janković, Uglješa (Ревија за социјална политика/Journal of Social Policy, 2015)
Strategic approaches to the problem of poverty were identified as the objective solutions in other countries and the third world. The first strategy for the reduction of poverty in Montenegro was implemented in 2003. A few years later (2007), the Government of Montenegro created new strategy in which the concept of social inclusion was incorporated. Along with the implementation of the above strategic approaches were also carried out the reform of the education and social welfare, with the clear objective of facilitation the social inclusion of marginalized groups. The main subject of this study is the application of the method of time series analysis in determining the degree of efficiency of applied strategic approach. If the strategy adopted in 2003and 2007produced results, then we can identify them as the key points where there is a change in trend of indicators that we use to predict the level of poverty. We will use the two available measures and test key hypotheses, unemployment and number of users of social help support.